“Prosthetic” Memory, “Aftersights” of Memory, Memory “Easy to Consume”? A Few Words About Visual Remembrance of the Holocaust - Kowalska, Urszula (Poznańskie Studia Slawistyczne, 2017)
Discussion about the borders restricting (unavoidable today) aestheticization of memory about the Holocaust experience is still valid – in the article are recalled some different strategies of remembering the Holocaust in the art using photography. Two of the artistic projects (Powidoki by Zbigniew Libera and Pocztówki z Auschwitz by Paweł Szypulski) are using authentic photographs to initialize the discussion about trivialization of image, removing it from its original context and, at the same time, “blunting” the sensitivity of the recipient. The other two works (Auschwitz, co ja tu robię by Mikołaj Grynberg and Miejsca nieparzyste by Elżbieta Janicka) are suspended between conversation and silence (two classic poles of memory about the Holocaust). All of these works are disputing with “fixed” models and imaginary experiences, deconstructing pathos, they are talking about the blurring memories and manipulating with memory, about competition of different historic narrations and attempts at overtaking the past, passing the traumatic experiences of the war and the Holocaust to the next generations.